Disappearing expertise in clinical automation: Barcode medication administration and nurse autonomy. (10th September 2020) - Hong, Jennifer Y; Ivory, Catherine H; VanHouten, Courtney B; Simpson, Christopher L; Novak, Laurie Lovett
Abstract: Objective: Using the case of barcode medication administration (BCMA), our objective is to describe the challenges nurses face when informatics tools are not designed to accommodate the full complexity of their work. Materials and Methods: Autonomy is associated with nurse satisfaction and quality of care. BCMA organizes patient information and verifies medication administration. However, it presents challenges to nurse autonomy. Qualitative fieldwork, including observations of everyday work and interviews, was conducted during the implementation of BCMA in a large academic medical center. Fieldnotes and interview transcripts were coded and analyzed to describe nurses' perspectives on medication safety. Results: Nurses adopt orienting frames to structure work routines and require autonomy to ensure safe task completion. Nurses exerted agency by trusting their own judgment over system information when the system did not consider workload complexity. Our results indicate that the system's rigidity clashed with adaptive needs embodied by nurses' orienting frames. Discussion: Despite the fact that the concept of nurse as knowledge worker is foundational to informatics, nurses may be perceived as doers, rather than knowledge workers. In practice, nurses not only make decisions, but also engage in highly complex task-related work that is not well supported by process-oriented information technology tools. Conclusions: Information technology developers and healthcare organization managers should engage and better understand nursing work in order to develop technological and social systems to support it.